1: Eye Tracking Analysis as a Means of Evaluating Aesthetic Result Following Toe to Thumb Transfers. (July 2021) - Boonipat, Thanapoom; Elgendy, Tarek; Hebel, Nathan SD; Moran, Steven
Abstract : Purpose: Exceptional functional results can be obtained with toe to thumb transfers; however objective measures to evaluate the aesthetic outcome of a toe to thumb transfers remains elusive. Aesthetic evaluation of a reconstruction when performed by external raters or the patient, may be influenced by expert knowledge, emotional antecedent, or ethnic or regional bias. In this study, we were interested in determining the observers' instantaneous, reflexive responses to the toe to thumb transfer as determined by eye-tracking analysis. Methods: 13 patients with unilateral great toe to thumb transfers were photographed using a standardized technique. None had undergone secondary procedures that changed the appearance of the transferred toe. Both hands were photographed side by side in each image. A dorsal and palmar image was taken, producing 26 photos in total. 40 observers (Average age 41.39, 14-65 yo, 18 males, 22 females), blinded to the procedure, were asked to evaluate each image for symmetry between the hands. An infrared eye-tracking camera continuously recorded their eye movements. Participants were allowed to evaluate each image for 6 seconds. Data was evaluated to determine the percent of time that was devoted to evaluating each portion of the photograph. The percent time spent in each of the lookzones was recorded. Results: i) Observers spent an average of 17.7% of their time evaluating the reconstructed thumb compared to the entire bilateral hand. This was on average 63% more time looking at the reconstructed thumb compared to the normal control thumb. (p value<0.01) ii) Observers spent 43.9% of the time looking at the reconstructed thumb compared to the entire hand of the same side. They spent 31.6% of the time looking at the normal control thumb compared to the entire hand of the same side (p value<0.01, mean 0.36 seconds on the abnormal thumb (SD 0.439)), vs. mean 0.22 seconds on normal control thumb (SD 0.305); mean 0.82 seconds on abnormal hand (SD 0.45), mean 0.69 seconds on normal contralateral hand (SD 0.423); mean 0.74 on entirely normal bilateral hand (SD 0.41)). iii) Areas of significant attention as visualized by heatmaps representing where observers focus their attention include abnormal nailbed and scar tissue at the junction between the toe and native hand skin. Conclusion: The technique described above may represent a novel and objective technique for quantifying observers' gaze with respect to toe to thumb reconstructions and the un-altered contralateral thumb. It could be applied to other areas of hand reconstruction to help determine aesthetic outcomes. The present pilot suggests that symmetric nail size may be an area of importance for creating the sense of aesthetic success. Incorporation of this data into surgical counseling may assist the patient and medical team focus on surgical-decision making priorities.